1993
DOI: 10.1073/pnas.90.18.8591
|View full text |Cite
|
Sign up to set email alerts
|

Cytolytic activity of intestinal intraepithelial lymphocytes in germ-free mice is strain dependent and determined by T cells expressing gamma delta T-cell antigen receptors.

Abstract: We have compared the cytolytic activities and the cellular compositions of the inal lntraeplthellal lymphocyte (i-IEL) populations in three different combinations of conventional (CV) and germ-free (GF) mice. Cytolytic activity of i-EELs exps yS T-l antigen receptors (TCRs) b strain dependent in CV mice (high vs. low), and this straindependent variability b unaltered in the GF condition. Although absolute numbers of yv i-IELs are sightly decrased, the composition of CD8aa+ and CD4-CD8-subsets and the usage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 28 publications
(37 reference statements)
2
70
0
Order By: Relevance
“…This finding suggested that regional phenotypic specialization of IEL is an endogenous process, although an exogenous site-related effect of food antigens and dead bacteria in the autoclaved diet could not be excluded in the GF animals. However, the present study confirmed earlier observations that the introduction of a normal microbial flora causes a rapid expansion of TCRa/b þ IEL [9][10][11][12][13]. Despite this adoptive numeric response, which initially was most pronounced in the ileum (quicker establishment or higher load of gut bacteria?…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding suggested that regional phenotypic specialization of IEL is an endogenous process, although an exogenous site-related effect of food antigens and dead bacteria in the autoclaved diet could not be excluded in the GF animals. However, the present study confirmed earlier observations that the introduction of a normal microbial flora causes a rapid expansion of TCRa/b þ IEL [9][10][11][12][13]. Despite this adoptive numeric response, which initially was most pronounced in the ileum (quicker establishment or higher load of gut bacteria?…”
Section: Discussionsupporting
confidence: 91%
“…Phenotypes of LCA þ IEL in the jejunum, ileum and colon of germ-free rats conventionalized (CV) for 1 week (CV 1 ) compared with agematched GF rats (GF 1 ), 5-week CV rats (CV 5 ), and 12-week CV rats (CV 12 ) compared with GF control rats (GF 12 ), as determined by two-colour in situ immunofluorescence staining. Proportions of IEL expressing TCRa/b, CD8a, CD8b, CD4 and CD5 were sigificantly increased in the ileum (P < 0.01) and those of TCRa/b and CD8a in the jejunum (P < 0.02) of CV 1 , whereas TCRa/b þ , CD8a þ and CD8b þ IEL were significantly increased both in the jejunum and the ileum (P < 0.01) in CV 12 compared with GF 1 and GF 12 , respectively. In the colon all T cell subpopulations examined had increased significantly in CV 1 , but no differences were noted between CV 12 and GF 12 rats.…”
Section: Subpopulations Of Rat Iel Express the Nkr-p1 Moleculementioning
confidence: 94%
“…In the mouse intestine, the existence of microbes increases the number of αβ IEL, but has little effect on γδ IELs [12]. In addition, it has been reported that the stimulation of intestinal bacterium accelerates the turnover of the epithelial cells in the intestine of rodents [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…In mice the cellular composition of the IEL compartment varies greatly with age and conditions of maintenance (5,6). In general, the number of TCR␣␤ CD8␣␤ IELs increases with age and upon transfer of the mice from a germ-free environment to conventional conditions of maintenance, whereas the relative frequencies of TCR␥␦ IELs and CD8␣␣ IELs decrease under these conditions (7). Concomitant with the transfer of mice from germ-free to conventional conditions of maintenance, an increase in the constitutive cytotoxic activity of CD8␣␤ TCR␣␤ IELs is observed (5).…”
Section: Ntestinal Intraepithelial Lymphocytes (Iels)mentioning
confidence: 99%